Analysis Study Proportion of Labour Wages on Road Development Project in Indonesia - Rosmariani Arifuddin (International Association of Lowland Technology, 2021)
In a construction project, determining the amount of costproportion to the resource should be precise. This researchaims to analyze the proportion of labor wages, identifying therelationship between labor wage costs to contract value andmodel the proportion of these resources so that they can beused as a reference. The research variables consist of workerswage costs (X1), the artisan's wage cost (X2), and the cost ofthe wage (X3), each determined by the proportion of the valueof the project. From the results of data collection, the proportionof the use of cost for workers is 0.27%-4.34%, the cost of thehandyman is 0.1%-1.07% and the cost for the foremanamounted to 0.1%-3.91%. Based on a simple regressionanalysis the most influential variable on the contract value isthe cost of worker’s wages with a value of R2 of 12.3%. Theresult of a regression analysis indicates that any increase inlabor cost variables will be followed by increased contractvalue. From the results of the analysis, produced amathematical model of Y = 0274 X1 + 0079 X2 + 0097 X3